Engineering materials 1 : an introduction to properties, applications and design - Ashby, M. F. (Butterworth-Heinemann, 2012)
Widely adopted around the world, this is a core materials science and mechanical engineering text. Engineering Materials 1 gives a broad introduction to the properties of materials used in engineering applications. With each chapter corresponding to one lecture, it provides a complete introductory course in engineering materials for students with no previous background in the subject.